2019
DOI: 10.1073/pnas.1904818116
|View full text |Cite|
|
Sign up to set email alerts
|

Sugar starvation-regulated MYBS2 and 14-3-3 protein interactions enhance plant growth, stress tolerance, and grain weight in rice

Abstract: Autotrophic plants have evolved distinctive mechanisms for maintaining a range of homeostatic states for sugars. The on/off switch of reversible gene expression by sugar starvation/provision represents one of the major mechanisms by which sugar levels are maintained, but the details remain unclear. α-Amylase (αAmy) is the key enzyme for hydrolyzing starch into sugars for plant growth, and it is induced by sugar starvation and repressed by sugar provision. αAmy can also be induced by various other stresses, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…A recent study revealed that the transcription factor MYBS2 competes with MYBS1 for the same cis -element of the αAmy promoter and represses αAmy expression ( Figure 2 ). Via promoting or inhibiting the expression level of αAmy , the competition between MYBS1 and MYBS2 can regulate and maintain sugar within an appropriate range during germination and early seedling growth under sugar starvation stress [ 23 ].…”
Section: The Molecular Regulatory Pathway Of Anaerobic Germinationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study revealed that the transcription factor MYBS2 competes with MYBS1 for the same cis -element of the αAmy promoter and represses αAmy expression ( Figure 2 ). Via promoting or inhibiting the expression level of αAmy , the competition between MYBS1 and MYBS2 can regulate and maintain sugar within an appropriate range during germination and early seedling growth under sugar starvation stress [ 23 ].…”
Section: The Molecular Regulatory Pathway Of Anaerobic Germinationmentioning
confidence: 99%
“…Despite the sophisticated molecular mechanisms involved in the regulation of the anaerobic germination and seedling growth in rice, considerable progress on understanding the genetic, molecular and physiological basis of rice in response to submergence stress at the germination stage, has been achieved in the last few decades [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Here, we mainly focus on reviewing the molecular genetic mechanisms that regulate the metabolic adaptation of rice to anaerobic germination stress; we could not cover all the related advances due to space limitations.…”
Section: Introductionmentioning
confidence: 99%
“…However, no cold shock was reported during this period 57 . In rice, accumulation of α-amylase has been described during grain developmental heat stress or more generally abiotic stress 58 . As a result, there is an emerging hypothesis that severe and rapid temperature changes may trigger LMA.…”
Section: Discussionmentioning
confidence: 99%
“…Rice adh1 mutants with reduced ATP levels display decreased cell division and impaired coleoptile elongation under submergence (Takahashi et al, 2011). Both gain-and loss-offunction studies have revealed that aAmy3 is essential for submergence tolerance, but overexpression of this enzyme alone is insufficient to enhance submergence tolerance in rice seedlings (Chen et al, 2019). Higher fermentation rates, soluble carbohydrate content, and efficient energy use are important factors contributing to rice AG/ ASD abilities relative to other cereals (Mustroph et al, 2006).…”
Section: Reviewmentioning
confidence: 99%